Plasminogen activator inhibitor 1 (PAI1) promotes actin cytoskeleton reorganization and glycolytic metabolism in triple negative breast cancer - Humphries, Brock (Mol Cancer Res, 2019)
Migration and invasion of cancer cells constitute fundamental processes in tumor progression and metastasis. Migratory cancer cells commonly upregulate expression of plasminogen activator inhibitor 1 (PAI1), and PAI1 correlates with poor prognosis in breast cancer. However, mechanisms by which PAI1 promotes migration of cancer cells remain incompletely defined. Here we show that increased PAI1 drives rearrangement of the actin cytoskeleton, mitochondrial fragmentation, and glycolytic metabolism in triple negative breast cancer (TNBC) cells. In two-dimensional environments, both stable expression of PAI1 and treatment with recombinant PAI1 increased migration, which could be blocked with the specific inhibitor tiplaxtinin. PAI1 also promoted invasion into the extracellular matrix from co-culture spheroids with human mammary fibroblasts in fibrin gels. Elevated cellular PAI1 enhanced cytoskeletal features associated with migration, actin-rich migratory structures and reduced actin stress fibers. In orthotopic tumor xenografts, we discovered that TNBC cells with elevated PAI1 show collagen fibers aligned perpendicular to the tumor margin, an established marker of invasive breast tumors. Further studies revealed that PAI1 activates ERK signaling, a central regulator of motility, and promotes mitochondrial fragmentation. Consistent with known effects of mitochondrial fragmentation on metabolism, fluorescence lifetime imaging microscopy (FLIM) of endogenous NADH showed that PAI1 promotes glycolysis in cell-based assays, orthotopic tumor xenografts, and lung metastases. Together, these data demonstrate for the first time that PAI1 regulates cancer cell metabolism and suggest targeting metabolism to block motility and tumor progression. IMPLICATIONS: We identified a novel mechanism through which cancer cells alter their metabolism to promote tumor progression.